Meriones unguiculatus serves as a spontaneous primary aldosteronism rodent model. - Mei You; Zongshi Lu; Bowen Wang; Min Liu; Qing Zhou; Li Li; Dan Tong; Yu Zhao; Hexuan Zhang; Zhongping Bai; Lijuan Wang; Tingbing Cao; et al. (PLoS ONE)
Background Primary aldosteronism (PA) is the most common form of endocrine hypertension. The available animal models of PA rely on gene manipulation, thus fail to duplicate the general pathological process of PA in humans. Meriones unguiculatus (MU) has been reported to possess a large size of adrenal gland and an elevated ability to save water. In this study, we aimed to confirm whether MU can serve as an ideal animal model of PA. Methods Sprague Dawley rats of the same body weight (SD1) or age (SD2) as MU were used as control groups. Blood pressure and serum aldosterone, renin and electrolyte levels were measured, and the oral salt loading test was used as confirmatory test to compare the inhibition level of the renin angiotensin aldosterone system (RAAS) among the three groups. The expression and distribution of CYP11B2 (aldosterone synthase) were evaluated in the adrenal gland of each group. Results MU exhibited typical clinical manifestations of PA, including hypertension, hyperaldosteronism, low renin levels and strong sodium retention and potassium excretion abilities. Compared with control groups, the inhibitory effect of a high-sodium diet on the RAAS was milder in MU, accompanied by significant cardiac dysfunction. The protein expression level and distribution area of CYP11B2 were significantly increased in the adrenal gland of MU. Conclusion The current study reveals that MU could serve as an ideal spontaneous PA model. The increased expression and distribution of CYP11B2 stimulate the excessive aldosterone production in a renin-independent manner, leading to a significant increase in blood pressure in MU.